Negotiation: A Strategic Tool For Bouncing Business Arena - Dr. Prema S.; Dr. Aruna Arputhamalar (International Journal of Economics, Business and Innovation Research, 2022)
Negotiation is an important factor in the process of decision-making and communication. Amidst a complex working environment, there is a dire need for negotiation skills amongst the working community. The subtle mix of skills namely listening, questioning, confidence, and creditability are the dire need of society to succeed in the business. For a successful business startup, negotiation technique plays an effective and efficient role. Good negotiation technique aims in building better relationships. In addition, it also intends to provide quality solutions to the existing problems that arise in the business environment. It soothes future problems and conflicts. This inherent quality enhances business understanding amongst the society. This article tries to analyze the necessity for negotiation techniques in the world of business communication. Further, it draws the importance and analyzes the strategic need for negotiation as a great asset in today's business world.